2008
DOI: 10.1007/s11606-008-0819-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Substance Use Education Among Generalist Physicians: An Evaluation of the Chief Resident Immersion Training (CRIT) Program

Abstract: This intensive training for chief residents (CRs) improved knowledge, confidence, and preparedness to diagnose, manage, and teach about substance use (SU), affecting both the CRs' SU clinical and teaching practices. The CRIT program was an effective model for dissemination of SU knowledge and skills to educators in a key position to share this training with a broader audience of medical trainees. This model holds potential to address other high priority medical, yet under-addressed, content areas as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 42 publications
2
43
1
1
Order By: Relevance
“…Several studies have shown that even short courses could increase knowledge on addiction medicine [36,37,38,39,40]. Moreover, courses have also been shown to induce more professional perceptions of and attitude toward patients with SUDs [36,37,38,39,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that even short courses could increase knowledge on addiction medicine [36,37,38,39,40]. Moreover, courses have also been shown to induce more professional perceptions of and attitude toward patients with SUDs [36,37,38,39,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that even short courses could increase knowledge on addiction medicine [36,37,38,39,40]. Moreover, courses have also been shown to induce more professional perceptions of and attitude toward patients with SUDs [36,37,38,39,41,42,43,44]. These studies cover the full range of undergraduate level [32,36,38,40], general physician level [37,39,40,42,43,44,45] and addiction specialist level [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on the ideal duration of such specialised training. Studies report variable duration from two and a half days to four days for training to be effective (Alford et al, 2009;Gunderson, Levin, & Owen, 2008). This study showed that a period of five days was sufficient to improve the knowledge and attitude of participants immediately after training.…”
Section: Discussionmentioning
confidence: 72%
“…Also needed are efforts to disseminate educational programs that have already shown the capacity to create clinician-educators who can teach geriatrics and chronic care, such as the Curriculum for the Hospitalized Aging Medical Patients (CHAMP) program for hospitalists, 39 the Chief Resident Immersion Training (CRIT) program for chief residents and program directors, 40,41 and the federal Health Resources and Services Administration's (HRSA's) Geriatric Academic Career Awards (GACA) for young geriatricians.…”
Section: Changes In Geriatricsmentioning
confidence: 99%